N2 and M2 lunar tides: atmospheric resonance revisited - D. M. Schlapp (Annales Geophysicae, 1996)
A numerical model has been used to calculate the atmospheric response to forcing at periods in the region of 12-13.5 h. The results show that the response is enhanced in the neighbourhood of 13 h. These results have been compared with lunar tidal analyses of mesospheric wind data and geomagnetic variations at a number of stations. It is found that the N2 lunar tidal component (period 12.66 h) is significantly enhanced relative to the main lunar tidal component M2 (period 12.42 h) in both types of data, compared with what would be expected from the gravitational tidal potential. This supports the predictions of the numerical model. An appreciable phase shift is also found in the experimental data between the N2 and M2 tides, agreeing in sense with what would be expected for a resonance at a period around 13 h.